4. RESULTS OF VACCINATION AGAINST COVID-19 FOR CHILDREN FROM 5 TO UNDER 12 YEARS OLD IN GO VAP DISTRICT, HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2023)
Objectives: Describe the results of the administration of vaccination against COVID-19 for children from 5 to under 12 years old and some influencing factors in Go Vap district, Ho Chi Minh City. Methods: A descriptive cross-sectional design, combining quantitative and qualitative research, was conducted on 36 vaccination sites in 16 wards, Go Vap District, Ho Chi Minh City, from May 2022 to December 2022. Results: Surveying 36 vaccination sites, 86.2% of vaccination sites had a waiting area vaccination with enough seats and ventilation, 100% of injection sites had enough vaccination equipment, 94.3% of vaccination sites had all medical staff who had been trained in vaccination against COVID-19, 76.2% of health workers performed well at the screening stage, 70.1% of staff Health workers performed well in vaccination consultation, 93.6% of health workers performed well in vaccine preparation for vaccination, 71.2% of health workers performed well in the vaccination stage, and 73.4% of health workers performed well in the post-vaccination stage. Conclusion: Medical staff must strictly follow the screening process, provide advice on vaccination, vaccinate, and guide parents to monitor post-injection reactions at the injection site and at home.
Keywords: Immunization, vaccines, Covid-19, children under 12 years old.